This I Believe - Perry, Ralph Barton (Tufts Archival Research Center, 2006)
Professor Emeritus of Harvard University, Ralph Perry describes his belief in believing - the quality that transforms idle thinking into action and his belief that humans can distinguish between right and wrong.